Cultural Sense Analysis of Reading Text for the Seventh Grade in the Junior High School English Textbook: â€œEnglish for Nusantaraâ€ - Ramadhani, Zakia; Refnaldi, Refnaldi (Universitas Pendidikan Mandalika, 2024)
Cultural sense in English textbooks is essential for fostering cultural sensitivity, developing cross-cultural communication skills, promoting cultural competence, encouraging critical thinking, and enhancing cultural literacy, This research aims to investigate the cultural sense represented in the textbook entitled